Visión empresarial como nuevo aporte a la teoría beckeriana del crimen en el Perú - Lizarzaburu Bolaños, Edmundo Raúl (2019)
This paper aims to approach crime of economic motivation as a wrong business model. The objective is to consider crime as an activity with the same goals of an enterprise. Therefore, this is a matter of study of business management, too: profit maximization through the cost minimization connected to the completion and maintenance of its operations; competiveness and influence of an appropriate climate for increasing its operations, for producing incomes illegally and having crime as collateral. The methodology conducted a historical review based on the Theory of the Rational Crime (Becker, 1968) and other theories that explain the benefits and incentives that make criminal business sustainable. The result underscores the tools introduction of the business administration sciences for understanding the criminal matter of economic motivation.